Sosyal Baskınlık Yönelimi, Yeme Tutumları ve Duygusal İştah: Kesitsel Bir Çalışma (Üçüncü Sektör Sosyal Ekonomi Dergisi, 2026)
This study aimed to examine the relationship between social dominance orientation (SDO), emotional appetite, and eating attitudes among political party members during the election period, which is characterized by increased psychosocial stress and changes in daily routines. A total of 631 participants (mean age 34.02±12.73 years) completed the Social Dominance Orientation Scale (SDO7), Emotional Appetite Questionnaire (EMAQ), and Eating Attitudes Test (EAT-26) through face-to-face interviews. The findings revealed that individuals with higher SDO scores exhibited lower emotional appetite and reduced “eating preoccupation” in negative emotional situations (p
Keywords: Sosyal Baskınlık; Yeme Davranışı; Duygusal Yeme; Psikolojik Stres; Yeme Tutumu